Real wages in Colombia: a conditional convergence analysis: 1984-20091 - Galvis, Luis Armando (Sociedad y Economía, 2011)
This study aims to study conditional sigma convergence using micro data. To this end, we use Colombian household surveys from 1984 to 2009 to calculate real wages for private sector employees. These data are used to calculate the share of total inequalities, measured by Theil index that can be attributed to interregional disparities. Bootstrapping methods are used to calculate confidence intervals for the interregional component of the Theil index. Results indicate that this component is statistically significant, and that it has not reduced through time. Thus, the findings do not support the convergence hypothesis in this respect. Results from a Mincer-type model that is used to study the microeconomic determinants of wages indicate that, after controlling for those determinants in the wage equation, significant differentials still remain. This provides evidence to reject the hypothesis of conditional sigma convergence in real wages for the main cities in the country.